Rancang Purwarupa Aplikasi Pendukung Keputusan Pemilihan Jurusan Bagi Mahasiswa dengan Pendekatan Design Thinking - Michael; Charlitos, Ralfpiere; Sudiono; Thang, Susanti (Journal of Digital Ecosystem for Natural Sustainability, 2021)
The purpose of this study is to design an application prototype that can help all the incoming student to know their inner self and choose the best major according to their skill. This research is a qualitative research with a Design Thinking approach. The Design Thinking approach has five stages namely emphatize, define, ideate, prototype, and test. Design Thinking Approach is an approach used to create innovation by focusing on "Human Centered Design". Data collection methods that going to be used in this study are online survey. The end result of this study are the ARJUS prototype application which has four main function, namely personality test, major recommendation, university recommendation, scholarship information.